2015
DOI: 10.1007/s00253-015-6847-z
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of oxidized glutathione fermentation by thiol redox metabolism engineering in Saccharomyces cerevisiae

Abstract: Glutathione is a valuable tripeptide widely used in the pharmaceutical, food, and cosmetic industries. In industrial fermentation, glutathione is currently produced primarily using the yeast Saccharomyces cerevisiae. Intracellular glutathione exists in two forms; the majority is present as reduced glutathione (GSH) and a small amount is present as oxidized glutathione (GSSG). However, GSSG is more stable than GSH and is a more attractive form for the storage of glutathione extracted from yeast cells after ferm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…These results suggest that the Erv1 protein directly oxidized GSH in S. cerevisiae cells. The suppression of GSSG production by the simultaneous over-expression of ERV1 and MIA40 genes in our previous study [15] and the much lower oxidation activity of Mia40 for GSH [25] also support this idea.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…These results suggest that the Erv1 protein directly oxidized GSH in S. cerevisiae cells. The suppression of GSSG production by the simultaneous over-expression of ERV1 and MIA40 genes in our previous study [15] and the much lower oxidation activity of Mia40 for GSH [25] also support this idea.…”
Section: Discussionsupporting
confidence: 52%
“…In a series of studies, the active residues, cofactor binding residues, and three-dimensional structures of Erv1 have been revealed [23, 27, 28]. In our previous study, we first focused on the ERV1 gene for biomaterial production, and revealed that over-expression of the ERV1 gene enhanced GSSG and total glutathione production in S. cerevisiae cells [15]. In this study, we also first improved Erv1 for biomaterial production and revealed that S32 and N34 residues are critical for oxidation of GSH and protein stability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glutathione Overexpression of YAP1 [58] Manipulation of the sulphate assimilation pathway by overexpressing MET14 and MET16 [59] Improved oxidized glutathione production by overexpression of GSH1, GSH2, and ERV1 and the deletion of GLR1 [60] Adaptive laboratory evolution in the presence of increasing levels of acrolein and screening for enhanced glutathione production [61] Whole-genome engineering via genome shuling and screening for enhanced glutathione production [62] Artemisinin/artemisinic acid Reconstruction of the complete biosynthetic pathway of artemisinic acid, including the three-step oxidation of amorphadiene to artemisinic acid by expression of CYP71AV1, CPR1, CYB5, ADH1 and ALDH1 from Artemisia annua [48] Taxol/taxadiene Expression of a truncated version of the endogenous tHMG1 and GGPPS from Taxus chinensis or Sulfolobus acidocaldarius together with TDC1 from T. chinensis [66] Prediction of the eiciency of diferent GGPPS enzymes via computer aided protein modelling [67] Forskolin Expression of a promiscuous cytochrome P450 from Salvia pomifera [68] Polyketides Heterologous expression of 6-MSA synthase gene from Penicillium patulum together with PPTases from either Bacillus subtilis or Aspergillus nidulans [69] Construction of polyketide precursor pathways by expressing prpE from Salmonella typhimurium and PCC pathway from Streptomyces coelicolor [70] Enhanced cofactor supply by expressing 2-PS from Gerbera hybrida [71] Resveratrol Reconstruction of a de novo pathway by expressing TAL from Herpetosiphon aurantiacus, 4-CL1 from Arabidopsis thaliana and VST1 from Vitis vinifera [49] Expression of 4CL1 from A. thaliana and STS from Arachis hypogaea [73] Expression of PAL from Rhodosporidium toruloides, C4H and 4-CL1 from A. thaliana, and STS from A. hypogaea [74] Expression of 4-coumaroyl-coenzyme A ligase (4CL1) from A. thaliana and stilbene synthase (STS) from V. vinifera [75] Overexpression of the resveratrol biosynthesis pathway, enhancement of P450 activity, increasing the precursor supply for resveratrol synthesis via phenylalanine pathway [76] Dihydrochalcones Expression of the heterologous pathway genes in a TSC13-overexpressing S. cerevisiae strain [78] Alkaloids Expression of 14 monoterpene indole alkaloid pathway genes from Catharanthus roseus and enhanced secondary metabolism to produce strictosidine de novo [79] Construction of the complete de novo biosynthetic pathway to norcoclaurine by expressing a mammalian TyrH enzyme and DODC from Pseudomonas putida, along with four genes required for biosynthesis of its electron carrier cosubstrate …”
Section: Representative Studies and Their Strain Improvement Strategymentioning
confidence: 99%